Aplikasi Penggunaan Kaedah Al-Darurah Tubih Al-Mahzurat dalam Penggunaan Ubat Pencair Darah bagi Wanita Mengandung dan Bersalin: Application Al-Darurah Tubih Al-Mahzurat Method in the Use of Anticoagulant for Pregnant and Postpartum Women - Mohd Zainun, Nur Suhada; Pauzi, Norhidayah; Abdul Wahab, Raihana (Al-Basirah Journal, 2024)
This study aims to examine the application of the al-Darurah Tubih al-Mahzurat method in the use of blood thinners for pregnant women. The al-Darurah Tubih al-Mahzurat method was introduced as an alternative approach in addressing the need for medications during pregnancy by emphasizing the safety and effectiveness of the use of blood thinners in this group. This study involves a review of literature studies and analysis through a comparative and inductive approach to the qawaid fiqhiyyah used in resolving this dilemma. The results of the study show that the use of the al-Darurah Tubih al-Mahzurat method allows blood thinners to be used by pregnant women and after childbirth when there is an urgent need such as the risk of thrombosis or more serious complications that can threaten the lives of the mother and baby. The analysis found that the balance of considerations maslahah and mafsadah is the main pulse in determining the ruling on the use of the medication. This study found that this method, al-Darurah Tubih al-Mahzurat, is very suitable for application in resolving this dilemma as well as providing practical guidance in maintaining the health of pregnant women and after childbirth.